Intensification of the use of production resources of industrial enterprises as factor them economic development - Oleksandr Yemelyanov; Tetiana Petrushka (Cхід, 2013)
Essence and features of economic development of enterprise is found out in the article. Grounded index of measure of intensity of production process after the certain type of resources of enterprise and certainly general sign of intensive type him economic development. Conformities to law of rational application of resources of enterprises are set. The method of determination of optimum level of intensification of the use of production resources is developed.